Perencanaan Pengembangan Industri Asbes Dengan Metode Analytical Hierarchy Process dan Linear Goal Programming - Muhammad Baderru Syarif; Ahmad Fikri Ramadhan (RESWARA: Jurnal Riset Ilmu Teknik, 2023)
The asbestos industry faces complex strategic planning challenges due to economic, environmental, technical, and social considerations. Effective industrial development planning requires a systematic decision-making approach capable of accommodating multiple and often conflicting objectives. This study aims to develop an integrated planning model for asbestos industry development using the Analytical Hierarchy Process (AHP) and Linear Goal Programming (LGP). AHP is employed to determine the relative importance of development criteria based on expert judgments, while LGP is used to optimize development strategies under multiple goals and constraints. The research adopts a quantitative decision-support approach, involving data collection through expert interviews, questionnaires, and secondary industrial data. The results indicate that environmental safety, economic feasibility, and technological readiness are the most influential criteria in asbestos industry development planning. The LGP model successfully generates optimal development scenarios that balance production targets, cost limitations, and environmental considerations. This integrated AHP–LGP approach provides a robust decision-making framework for policymakers and industry stakeholders in planning sustainable asbestos industry development. The study contributes theoretically by enriching multi-criteria decision-making applications in industrial planning and practically by offering a structured tool for strategic industrial development decisions.